Step 1 →Consider each inequality constraint as equation.
Step 2 →Take one variable (say x) in a given equation equal to zero and find the value of other variable (say y) by solving that equation to get one co-ordinate [say (0, y)] for that equation.
Step 3 →Take the second variable (say y) as zero in the said equation and find the value of first variable (say x) to get another co-ordinate [say (x, 0)] for that equation.
Step 4 →Plot both the co-ordinates so obtained [i.e., (0, y) and (x, 0)] on the graph and join them by a straight line
I think this is the answer to your question, right? yeah...........right!
I hope. =(((((